Supply Chain Management (SCM) Analysis in the Distribution Flow of 3 Kg LPG Gas at UD. Fitri Depot in Karo Regency - Nikira, Nikira; Rahmani, Nur Ahmadi Bi; Lubis, Fauzi Arif (Amkop Management Accounting Review (AMAR), 2025)
The purpose of this study is to investigate the stages of the supply chain process involved in distributing 3 kg LPG gas at the UD distribution center in Karo Regency, as well as to identify the causes of delays in delivery and reductions in the quantity of goods requested by retailers at the distribution center. Fitri in Karo Regency, as well as to identify the causes of delivery delays and reductions in the quantity of goods requested by retailers at the distribution center. The method used in this study is a qualitative survey analysis, conducted through Lean Search, based on direct observation at the LPG gas distribution center. Data collection techniques included observation, interviews, and documentation conducted directly at the gas distribution center. The results of the study indicate that the 3 kg LPG gas distribution center is located at UD. Fitri in Karo Regency has three supply chain flows: product flow, information flow, and financial flow. Delays in the delivery of goods from the distribution center to retailers are caused by transportation limitations of the distribution center, which cannot transport large quantities of LPG gas to multiple retailers at once, as well as transportation issues such as flat tires and the distance between the distribution center and retailers, and unexpected road conditions that occasionally cause traffic congestion, leading to delays in goods delivery. Additionally, discrepancies between the quantities ordered by retailers and those delivered by the distribution center are caused by the limited supply available at the distribution center, which must allocate the available LPG gas among multiple retailers. Based on the analysis conducted by the author, the LPG distribution center UD. Fitri should establish and implement a scheduling system for retailers by dividing days and times for placing LPG gas orders. Additionally, the distribution center should consider the distance traveled for deliveries to retailers to minimize the risk of delivery delays. It should also calculate distribution costs for deliveries to retailers by avoiding and reducing excessively long distances, thereby saving on distribution costs in the event of fuel price increases while maintaining an efficient distribution process.